De l’oubli à la reconnaissance - Vanessa Auroy (Carnets)
The Second World War has become the topic of movies, books and other formats. Although many works (fictional or not) have been shot or published, not everything has been said or revealed about this very important event in History. Therefore, we are going to study Paco Roca’s comic strip La Nueve. Les républicains espagnols qui ont libéré Paris. The contemporary Spanish author tels the true story of republican Spanish refugees who joined the French Resistance against the Nazi German occupation of France and the Vichy Regime and who took part in the liberation of the French capital city. This graphic novel tells us about their incredible route from their escape of Nationalist Spain in early 1939. The novel gives the opportunity to pay tribute to these men who have entirely been forgotten by History.